Effectiveness of Panretinal Photocoagulation in Treatment of Diabetic Retinopathy - Dijah Dijah; Erwin Iskandar; Ine Renata Musa (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Diabetic retinopathy is leading cause of blindness, is preventable, in whole of the world. Panretinal photocoagulation is a well-established treatment to induce regression of new blood vessels in diabetic retinopathy. This study to assess effectiveness of panretinal photocoagulation in treatment of diabetic retinopathy.Methods: We enrolled in retrospective study, using data from medical records of patients with proliferative diabetic retinopathy and severe non proliferative diabetic retinopathy between 2009 and 2011, and were assessed for visual acuity and fundus stability minimal 6 weeks after panretinal photocoagulation complete.Results: Panretinal photocoagulation was perfomed in 435 eyes (295 patients), with proliferative diabetic retinopathy was recognized in 245 eyes, and severe non proliferative diabetic retinopathy in 190 eyes. In cases of patients with proliferative diabetic retinopathy stabilization of visual acuity was observed in 137 (55,92%) of eyes and stabilization of the eye fundus in 119 (48,57%) of eyes. In patients with severe non proliferative diabetic retinopathy stabilization of visual acuity was found in 141 (74,21%) of eyes and stabilization of state of the eye fundus in 147 (77,37%) of eyes.Conclusion: Panretinal photocoagulation as gold standart therapy effectiveness to treatment proliferative diabetic retinopathy and severe non proliferative diabetic retinopathy to adhered visual acuity stability dan fundus stability.